Síntese e caracterização de vidros cálcio boroaluminato dopados com Dy2O3 para geração de luz branca - LODI, Thiago Augusto (2018)
In this work visible luminescence of Dy3+-doped calcium boroaluminate (CaBAl) glasses has been studied. The samples were prepared by melt-quenching technique with different concentrations of Dy2O3, aiming understanding how the dopant changes the structural, thermal, spectroscopic and optical properties. The results of XRD confirmed the amorphous nature of the glasses studied. The values of the volumetric density (ρ) show an increase with Dy3+ content. The FTIR results showed that the vitreous network is formed by BO3 and BO4 structures, and that there was an increase in the number of NBOs with increasing Dy2O3 concentration. From DTA analysis was observed an increase in Tg and Tx values, as well as an increase in thermal stability with Dy2O3 content. The refractive index (n) values showed a tendency of increase with the increase of dopant concentration, but within the error. Absorption spectra present characteristic peaks of Dy3+, which are transitions from the 6H15/2 ground state to the excited energy levels. The luminescence spectra, under 365, 388 and 405 nm excitation, present two intense bands at 483 nm (blue) and 574 nm (yellow), corresponding to the transitions 4F9/2 → 6H15/2, 6H13/2, respectively. The intensity of Dy3+ emission spectra increases with Dy2O3 content from 0.5 wt% to 3 wt% and concentration quenching was observed for concentrations higher than 3 wt%. The yellow-blue (Y/B) emission intensity ratios and CIE chromaticity coordinates were calculated to evaluate white light emission as a function of the Dy2O3 content. The experimental lifetime decrease with increase of Dy2O3, due Dy3+-Dy3+ interaction. The nonexponential decay curves were well fitted to the IH model, for S = 6, indicating that the energy transfer between the Dy3+ ions is of the dipole-dipole type. The simulation of combination of a Blue LED (BL) emission with the samples emission was also studied in the CIE diagram, in order to evaluate the possibility of reaching a route for smart lighting. All results suggest that the investigated CaBAl:Dy3+ glasses are candidates for W-LEDs application and smart lighting.